2017
DOI: 10.3390/ma10111324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alumina Incorporation on the Surface Mineralization and Degradation of a Bioactive Glass (CaO-MgO-SiO2-Na2O-P2O5-CaF2)-Glycerol Paste

Abstract: This study investigates the dissolution behavior as well as the surface biomineralization in simulated body fluid (SBF) of a paste composed of glycerol (gly) and a bioactive glass in the system CaO-MgO-SiO2-Na2O-P2O5-CaF2 (BG). The synthesis of the bioactive glass in an alumina crucible has been shown to significantly affect its bioactivity due to the incorporation of aluminum (ca. 1.3–1.4 wt %) into the glass network. Thus, the kinetics of the hydroxyapatite (HA) mineralization on the glass prepared in the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…050453), and wollastonite (Ca 2 SiO 4 —JCPDS. 310299) . These HCA, HA, calcite, and wollastonite diffractograms characteristic patterns are matched with the obtained peaks.…”
Section: Resultssupporting
confidence: 75%
“…050453), and wollastonite (Ca 2 SiO 4 —JCPDS. 310299) . These HCA, HA, calcite, and wollastonite diffractograms characteristic patterns are matched with the obtained peaks.…”
Section: Resultssupporting
confidence: 75%
“…The chemical degradation tests performed earlier for BG1d-BG and BG-gly paste in Tris-HCl at 37 ∘ C in static regime without solution replacement revealed that mass loss after 120 h was 2.81 wt% and 28.46 wt%, respectively [40]. Considering that the BG-gly sample consists of 27 wt% glycerol, one can conclude that relatively fast dissolution of glycerol from glass surface occurs.…”
Section: Properties Structural Features and Bioactivity Of Bg1d-bg Amentioning
confidence: 77%
“…ca. 25 and 50% higher concentrations, respectively, after 3 h immersion in SBF [40]). The enhanced dissolution of Ca 2+ and Mg 2+ is governed by surface chemistry and is due to significant fraction of Q 1 and Q 0 units in the BG-gly material (Table 3).…”
Section: Properties Structural Features and Bioactivity Of Bg1d-bg Amentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the BG‐gly paste had a significantly higher bioactivity than as‐prepared BG during immersion in the SBF. This was attributed to the chemical interaction of gly with the surface of BG, which resulted in a strong decrease in the network connectivity of BG, as well as a significant increase in the number of silanol groups on the surface of the paste . Aho et al ., formulated injectable composites of BG S53P4 and poly(ε‐caprolactone‐ co ‐ d , l ‐lactide).…”
Section: Introductionmentioning
confidence: 99%